Students’ Perception toward Psychological Problems Faced in Public Speaking Class - Sulastiani (Journal La Edusci, 2020)
Students’ Perception toward Psychological Problems Faced in Public Speaking Class of English Department. (A Descriptive Research of Students at English Department Year 2015 at Muhammadiyah University of Makassar). This study aimed to find the students perception toward psychological problems faced in terms of fear and anxiety in public speaking class of English department. The data was collected from Fourth semester students of English Department who learned Public Speaking Subject. This study used descriptive qualitative research design. The instruments used were questionnaire and interview. The questionnaire was distributed to 40 students from different classes and based on the questionnaire scores the researcher took 10 students to be interviewed in order to know their perception. The questionnaire used was PSCAS (Public Speaking Class Anxiety Scale) and the interview used was semi structured interview. Based on findings, it was found that 33 of 40 or 82.5% students were indicated having medium level of fear and anxiety in public speaking class and 7 of 40 or17.5% students were having low level of fear and anxiety in public speaking class. Furthermore, it was found that the students gave negative perception toward psychological problems faced in public speaking class of English department. Moreover, there were several factors of students’ public speaking class fear and anxiety, those were fear of making mistakes, feeling that their friends would laugh at them, fear when looked at the audiences’ eyes, though that other students were better than them, and students did not have good preparation. Students perceived that public speaking class fear and anxiety impact negatively toward their performance in public speaking class such as students forgot their speech preparation, students were confused and stop to speak, made the students uncomfortable to speak English in public speaking class.